FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA AKUNTAN - Purnamasari, Dian Indri (Jurnal Riset Akuntansi dan Keuangan, 2008)
The aim of this research is to find empirically the influence of workfamily con/lict, organizational culture, organizational commitment, ond leadership on accountant work satisfaction.'The respondents on this reseorch are drawn from all public occountant and accounting lecturer in Yogtakmta. The results show work family conflict and organizational culture does not influence accountant work satisfaction, however organizational commitment and leadership inJluence accountant work satisfactionKeywords : Work-family conflict, comitment, leadership, accotmtant